PERAN PEREMPUAN DALAM MENINGKATKAN EKONOMI KELUARGA MELALUI KEGIATAN UMKM DI DESA WIRODITAN - Nida Aqbila; Hendri Hermawan Adinugraha; Muhammad Shulthoni (Journal of Islamic Economics (JoIE), 2024)
Introduction: In the ever-evolving digital age, significant social changes have transformed the roles and contributions of women in society. Women are not only required to fulfill their responsibilities as mothers and wives, but also to pursue careers and overcome the challenges that arise from dual demands. Women's involvement in the workforce can have a positive impact on the family economy, such as improved welfare through the acquisition of relevant resources and knowledge. But on the other hand, the increased workload can also reduce the time they have for family. This study aims to find out more about the role of women in improving the family economy through MSME activities in Wiroditan village. The research employs a qualitative approach with a descriptive method, including observation, interviews, and documentation. Results: This paper shows that economic activities that are possible to be carried out by women are the Micro, Small and Medium Enterprises (MSMEs) sector where there are at least two main reasons for choosing these businesses, namely the lack of capital and the type of business that can be done at home so that it does not require additional capital to rent a business location. Conclusion: This study explains that housewives and women in Wiroditan Village rely on their trading skills to supplement household income. Only a few of them have skilled jobs in various industries.